Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Get accurate and detailed answers to your questions from a dedicated community of experts on our Q&A platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
Answer:
5 + 2x = 6
2x = 6-5
2x = 1
x = 0.5
n -3n = 14 -4n
-2n = 14-4n (since 4n is negative, change the sign to make it positive and then add 4n to both sides of the equation)
2n = 14
n = 7
7 (5a - 4) - 1 = 14 - 8a
35a - 28 - 1 = 14 -8a
35a -29 = 14 - 8a
43a = 43
a = 1
Step-by-step explanation:
1.
5 + 2x = + 6
2x=6-5
2x=1
[tex]x \ = \frac{1}{2} [/tex]
2.
n - 3n = 14 - 4n
-2n= 14 -4n
-2n+4n=14
2n=14
n=7
3.
7(5a - 4 ) - 1 = 14 - 8a
35a-28-1=14-8a
35a-29=14-8a
35a+8a=14+29
43a=43
a= 1
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.